Lymphocytic myocarditis with suspected granulomatosis with polyangiitis presenting as cardiogenic shock, restrictive cardiomyopathy and complete heart block. Issue 3 (September 2021) - Anderson, Wesley L.; Bahrami, Mubashir H.; Guglin, Maya; Rao, Roopa
Abstract: We report a case of restrictive cardiomyopathy from lymphocytic myocarditis in a patient with suspected granulomatosis with polyangiitis (GPA). The case was complicated by complete heart block and renal failure. The diagnosis was supported by upper airway involvement, elevated serum serine proteinase 3 antibodies, and endomyocardial biopsy with lymphocytic infiltration. The patient responded appropriately to aggressive immunosuppressive therapy. <Learning objective: Our case reviews an atypical presentation of lymphocytic myocarditis and likely cardiac granulomatosis with polyangiitis (GPA). We also demonstrate an evaluation of restrictive physiology as well as discuss the presentations and management of cardiac GPA with its response to immunotherapy.>